Understanding the Function of Present Perfect Tense through EGRA Implementation in EFL Classroom - Heriyanti Tahang (Universitas Muhammadiyah Sorong, 2020)
This study focused on investigating the effectiveness of EGRA (Experience, Generalization, Reinforcement, Application) technique implementation in improving the ability of college students at London School English Center to understand the usage of the present perfect tense. The study used a true Experimental method with a pretest-posttest control group design. The population was all the college students studied in London school. It was 45 students. The sample was taken using random sampling. It was 24 students divided into two classes. The experimental group was 12 and the rest 12 students were as the control group. The N-gain calculation was used to know the effectiveness of the EGRA implementation in improving students' ability to understand the usage of the present perfect tense. The N-gain result showed I percentage mean. The calculation result showed 65.45 %. It meant that the implementation of EGRA techniques reached the Effective Enough category. It was revealed that the use of EGRA technique was effective enough to enhance the students 'understanding of the usage of the present perfect tense. While the result of N-gain for Control group was 21.41% mean. It showed that the application of the conventional method (Explanation and practicing) was not effective in improving students' ability to understand the usage of the present perfect tense.